Evaluation of the Companies’ Performance: A Study on Mobile Telecommunication Companies in Bangladesh - Neogy, Taposh Kumar (American Journal of Trade and Policy, 2014)
In the evaluation of the operating results of the selected mobile telecommunication companies, it is evident that the Company # 1 could earn good profit during the study period but the performance of Company # 2 is not satisfactory because it has been continuously facing loss for the last several years with the exception of 2011. The operating performance of Company # 1 is better than that of Company # 2 during the period under study. In addition, some hypotheses have developed regarding the operating results and all hypotheses are rejected which indicate that there is significant difference in operating results of the selected mobile telecommunication companies during the period under study.